Pelatihan Cyber Grooming bagi Guru BK sebagai Upaya Penguatan Perlindungan Siswa di Era Digital - Dini Rakhmawati; Chr Argo Widiharto; Heri Saptadi Ismanto; T Sri Suwarti (Perkumpulan Kualitama Edukatika Indonesia, 2026)
Cyber grooming has become a growing digital threat to adolescents, requiring school counselors to possess adequate knowledge and intervention skills. However, many guidance and counseling teachers still have limited understanding of cyber grooming characteristics, perpetrators’ strategies, and victim handling procedures. This community service program aimed to improve the competence of school counselors through training based on the Detection, Intervention, and Education (DIE) Model. The participants were 27 guidance and counseling teachers from SMP, MTs, SMA, SMK, and MA schools who are members of MGBK and PD ABKIN Banjarnegara. The program was implemented using a Participatory Technological Learning approach consisting of workshops, mentoring, and evaluation activities. Program effectiveness was measured through pre-test and post-test assessments and analyzed using paired-sample t-tests. The results showed a significant improvement in participants’ overall understanding of cyber grooming (t = 5.831, p < .001). Significant increases were also found in understanding social media grooming, recognizing grooming tactics on popular digital platforms, and applying crisis counseling techniques for victims. These findings indicate that the training effectively enhanced counselors’ readiness to identify, prevent, and respond to cyber grooming cases in schools. The program also supported the development of digital student protection initiatives through the preparation of early detection tools and school-based protection procedures.